2015
DOI: 10.4269/ajtmh.14-0492
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Blastocystis Infection Among Children and Caregivers in a Child Care Center, Bangkok, Thailand

Abstract: Abstract. In September 2009, a cross-sectional study was conducted to evaluate parasitic infections in a child care center in Khlong Toei, Bangkok, Thailand. Of 503 children and staff members, 258 (51.3%) stool samples and questionnaires were obtained. The most common parasitic infection was Blastocystis sp. (13.6%). Blastocystis sp. subtype 3 was predominantly found (80.0%), followed by subtypes 2 (12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
6
1
2
Order By: Relevance
“…The most common subtype found in all regions was subtype 3 (46%–100%) (Table 3 and Figure 7). Our results were consistent with the previous studies in Thailand that reported subtype 3 as the dominant subtype (53.2%–80%) in different populations [11,46,52,64,65]. However, our results were different to some studies that report subtype 1 as the major subtype (77.9%–100%) [10,38,55].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most common subtype found in all regions was subtype 3 (46%–100%) (Table 3 and Figure 7). Our results were consistent with the previous studies in Thailand that reported subtype 3 as the dominant subtype (53.2%–80%) in different populations [11,46,52,64,65]. However, our results were different to some studies that report subtype 1 as the major subtype (77.9%–100%) [10,38,55].…”
Section: Discussionsupporting
confidence: 87%
“…Our data were consistent with several studies, which show that Blastocystis infections are common among children in Thailand. This prevalence was higher than the prevalence in adults (14.5%–37.2%) [10,11,12] and in children in Bangkok (13.6%–31.9%) [38,52], but slightly lower than in children in orphanage (45.2%) [53]. This may be due to the overcrowded environment and poor sanitation in the orphanage.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of B. hominis in our study was lower than that previously reported among schoolchildren from seven provinces, which was in the range of 7.9% to 80.2% [9,14] using culture method for detection. The difference in prevalence may be due to the culture method for B. hominis being more sensitive than the simple direct smear method and concentration techniques [9].…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, health education and environmental sanitation improvement are recommended as preventive control measures. from 2.3% to 37.7% in Thai children [6][7][8][9][10][11][12][13][14], but no studies on the epidemiology of infectious disease involved study of the prevalence of intestinal protozoan infections among schoolchildren from Bang Khla District, Chachoengsao Province. Therefore, the present study was conducted to determine the prevalence of intestinal parasitic infections among schoolchildren in rural areas from four primary schools at Bang Khla District, Chachoengsao Province in the central region of Thailand, using simple direct smear method and formalin ethyl acetate concentration technique.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan penelitian yang dilakukan Sari et al (2017) Blastocystis ST 1 dan 3 merupakan subtipe dominan yang ditemukan pada anakanak di Jakarta, Indonesia. Hasil penelitian tersebut juga sejalan dengan penelitian yang dilakukan di Thailand dan beberapa negara tetangga (Pipatsatitpong et al, 2015;Popruk et al, 2015;Palasuwan et al, 2016;Sanpool et al, 2017). Kejadian infeksi campuran pada manusia lebih tinggi dibandingkan dengan NHP (Suroiyah et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified